2016
DOI: 10.1371/journal.pone.0156305
|View full text |Cite
|
Sign up to set email alerts
|

Assimilating to Hierarchical Culture: A Grounded Theory Study on Communication among Clinical Nurses

Abstract: The purpose of this study was to generate a substantive model that accounts for the explanatory social processes of communication in which nurses were engaged in clinical settings in Korea. Grounded theory methodology was used in this study. A total of 15 clinical nurses participated in the in-depth interviews. “Assimilating to the hierarchical culture” emerged as the basic social process of communication in which the participants engaged in their work environments. To adapt to the cultures of their assigned w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 22 publications
1
23
0
Order By: Relevance
“…However, this study also extended the results of previous studies by further exploring the blurred boundaries between facilitators and barriers, influences from Chinese cultural impact and project leaders' roles, as well as an emphasis on the importance of point of care in evidence-based nursing. Second, this study showed a profound influence by the Chinese cultural values, which is characterised as assimilating to the system's culture and seeking harmony, following the power hierarchy and obedience to authority (Delury, 2008;Farh & Cheng, 2000;Kim & Oh, 2016;Lee, Hsu, Li, & Sloan, 2013). These intraconnected cultural values work interactively behind the scenes of Chinese evidencebased nursing practice .…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…However, this study also extended the results of previous studies by further exploring the blurred boundaries between facilitators and barriers, influences from Chinese cultural impact and project leaders' roles, as well as an emphasis on the importance of point of care in evidence-based nursing. Second, this study showed a profound influence by the Chinese cultural values, which is characterised as assimilating to the system's culture and seeking harmony, following the power hierarchy and obedience to authority (Delury, 2008;Farh & Cheng, 2000;Kim & Oh, 2016;Lee, Hsu, Li, & Sloan, 2013). These intraconnected cultural values work interactively behind the scenes of Chinese evidencebased nursing practice .…”
Section: Discussionmentioning
confidence: 82%
“…Second, this study showed a profound influence by the Chinese cultural values, which is characterised as assimilating to the system's culture and seeking harmony, following the power hierarchy and obedience to authority (Delury, ; Farh & Cheng, ; Kim & Oh, ; Lee, Hsu, Li, & Sloan, ). These intraconnected cultural values work interactively behind the scenes of Chinese evidence‐based nursing practice (Cheng et al., ).…”
Section: Discussionmentioning
confidence: 95%
“…Thus, it would be effective to encourage nurses to decide to provide patient care voluntarily to increase willingness to care for patients with EID. However, this might be challenging because of the vertical organizational structure in Korean nursing, and this hierarchical culture has made it difficult for Korean nurses to speak out (Kim & Oh, ). The majority of Korean nurses could not refuse instructions from their superiors or nurse managers when asked to care for MERS patients during the outbreak (Kim, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, this might be challenging because of the vertical organizational structure in Korean nursing, and this hierarchical culture has made it difficult for Korean nurses to speak out (Kim & Oh, 2016).…”
Section: Factors Influencing Nursing Intention To Care For Patientsmentioning
confidence: 99%
“…The variable on "displaying positive disposition in sharing views and opinions" receiving the lowest score may be attributed to the findings in a study done in South Korea that novice nurses preferred "peer opinion-sharing within horizontal relationships" [37]. Since coaching is done by their seniors, this aspect of the RICH strategy was not fully appreciated by novice nurses.…”
Section: Statement Of Thementioning
confidence: 99%